Salvaging Utopia: Lessons for (and from) the Left in Rivers Solomon’s An Unkindness of Ghosts (2017), The Deep (2019), and Sorrowland (2021) - Megen de Bruin-Molé (Humanities, 2021)
In response to this special issue’s question of whether mainstream science fiction has become stuck in presentism and apocalypticism, this article examines how utopia is expressed and salvaged in the work of Rivers Solomon. Using three of Solomon’s novels and the theoretical lenses of black utopia studies and salvage-Marxism, I suggest that scholars and activists should approach this question from a different perspective. While Solomon’s novels may seem dystopian from the perspective of liberalism or whiteness, they can also clearly be placed within the long, if marginalized, history of leftist and black utopian thought. Likewise, where the ‘traditional’ utopia (a concept I interrogate) is often imagined as grounded in hope and futurity, black utopia and salvage-Marxism reject these concepts as counterproductive to the actual work of social justice and utopia-building. Despite their presentism and apocalypticism, then, I argue Solomon’s novels are very much utopian: they simply locate their utopian desire in radical kinship and salvage, rather than universalism or futurity.